Foreign Policy and Defense Diplomacy in ASEAN to Maintain Stability and Security in the Indo-Pacific Region - Abdullah Zulkifli; Makarim Wibisono; Anak Agung Banyu Perwita; Jonni Mahroza (Publica: Jurnal Pemikiran Administrasi Negara, 2023)
The ASEAN Outlook on Indo-Pacific (AOIP) is intended to transform rivalries in the region into collaboration by prioritizing, among other things, maritime cooperation. AOIP influences Indonesia's defense diplomacy in ASEAN and the Indo-Pacific. The framework for defense diplomacy and maritime cooperation is used to analyze the role of AOIP in encouraging cooperation to increase stability and mutual trust. The defense diplomacy framework is used to analyze various Indonesian defense diplomacy policies in producing various agreements and cooperation in the field of defense and security. The maritime security cooperation framework is used to highlight various cooperation and activities to enhance maritime security in the Indo-Pacific region, and geopolitics to analyze the dynamics of global political and security developments, especially in the Indo-Pacific region. Indonesia by initiating the formation of AOIP encourages defense diplomacy to create stability and increase mutual trust, one of which is for maritime security cooperation. Obstacles that arise because the implementation of AOIP has not been carried out due to the pandemic and the complexity of various interests between actors (states), but Indonesia's defense diplomacy to produce defense cooperation remains wide open